2009
DOI: 10.1021/cg900109x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of High-Yield Gold Nanoplates on the Surface: Effective Two-Dimensional Crystal Growth of Nanoseed in the Presence of Poly(vinylpyrrolidone) and Cetyltrimethylammonium Bromide

Abstract: This paper reports a simple technique to grow high-yield gold nanoplates directly on the surface via an effective two-dimensional growth promotion of the attached nanoseeds in the presence of a binary surfactant mixture, namely, poly(vinylpyrrolidone) (PVP) and cetyltrimethylammonium bromide (CTAB). The gold nanoplates formation strongly depended on the concentration of PVP used in the solution, while the nanoplate size depended on the CTAB concentration. In a typical process with optimum PVP and CTAB concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 28 publications
6
58
1
Order By: Relevance
“…35−37 Working in concert with CTAB, iodide is believed to suppress the growth in [111], the direction normal to the top and bottom surfaces of a plate, while allowing for the incorporation of the gold atoms to the edges. 15,28 ITO substrates were directly immersed into a mixture of chloroauric acid, ascorbic acid, CTAB, and KI at an elevated temperature, 70°C. SEM images ( Figure 1A−C) showed that micrometer-sized plates were formed on ITO, and the sizes increased as the reaction time increased.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35−37 Working in concert with CTAB, iodide is believed to suppress the growth in [111], the direction normal to the top and bottom surfaces of a plate, while allowing for the incorporation of the gold atoms to the edges. 15,28 ITO substrates were directly immersed into a mixture of chloroauric acid, ascorbic acid, CTAB, and KI at an elevated temperature, 70°C. SEM images ( Figure 1A−C) showed that micrometer-sized plates were formed on ITO, and the sizes increased as the reaction time increased.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…10 We note that the parallel growth of plates was also observed in other studies that synthesized nanoplates. 28,29 The attractive interaction between gold microplates and ITO reduces the surface energy of the plates. Plates parallel to the surface are stabilized by the attractive interactions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1C). This phenomenon was also observed in the case of gold nanoplate growth using the HMT, where the increasing of HMT concentration produced a larger gold nanoplate size [24,25]. Effective c-axis plane passivation is considered as one of the reason in ZNPs size increment.…”
Section: Znps Synthesis and Characterizationsmentioning
confidence: 68%
“…And in the presence of the surfactant (HMT) here via an effective adhesion of its active amine functional onto the TiO 2 nanocrystallite, presumably on (001) plane, the nanorice of anatase TiO 2 that is bounded by this plane is realized. Such feature has also been found in the one-dimensional crystal growth in the case of ZnO [26,27] and platelet [28,29], brick-shape [30], nanofibrous [31,32] and multipods [33] nanocrystal in the case of Au, Pt and Pd. Therefore, in order to obtain the extent role of HMT in the formation of (001)-faceted TiO 2 nanorice, we examined the nanocrystal growth properties under a different HMT concentration.…”
Section: Tio 2 Nanorice Characterizationmentioning
confidence: 76%